Aging effect of atmospheric air on zirconia surfaces treated by nonthermal plasma - Dos Santos, Daniela Micheline [UNESP]; Vechiato-Filho, Aljomar José [UNESP]; Da Silva, Emily Vivianne Freitas [UNESP]; Goiato, Marcelo Coelho [UNESP]; Cesar, Paulo Francisco; Rangel, Elidiane Cipriano [UNESP]; Da Cruz, Nilson Cristino [UNESP] (My University, 2015)
Purpose: The purpose of this study was twofold: 1) to characterize the zirconia (Y-TZP) surfaces through scanning electronic microscopy associated with energy-dispersive spectroscopy and atomic force microscopy after the deposition of a thin organosilicon film by nonthermal plasma (NTP) treatment, and 2) to determine the zirconia surface hydrophilicity, before and after aging, through surface energy analysis. Materials and Methods: Surfaces of 16 zirconia disks (10 x 3 mm) were treated for 30 min each with hexamethyldisiloxane and argon plasmas, followed by oxygen plasma. Disks were analyzed before NTP treatment, immediately after NTP treatment, and after aging for 7, 15, and 30 days. The surface energy of the Y-TZP disks was measured with a goniometer. Quantitative data were submitted to statistical analysis using ANOVA and Tukey's test (p < 0.05). Results: Immediately after NTP treatment, the surface energy of the zirconia disks was significantly higher than at any other tested period (p < 0.001), and the water contact angle on the zirconia disks was reduced to 0 degrees. Similar surface energy results were obtained before NTP treatment and after 15 or 30 days of aging (p > 0.05; Tukey's test). Energy-dispersive spectroscopy results revealed the presence of carbon, oxygen, and silicon on the surface after NTP treatment. Conclusion: NTP treatment was useful for treating the zirconia surface for cementation procedures, as it produced a high level of hydrophilicity on the zirconia surface. However, this high level of hydrophilicity did not persist after aging.
Keywords: Contact angle; Microstructure; Nonthermal plasma; Surface energy; Surface topography; Y-TZP